Make It Inconsistent

Algebra Level 5

{ x + y = a x 2 + y 2 = b x 3 + y 3 = c \begin{cases} x + y = a \\ x^2 + y^2 = b\\ x^3 + y^3 = c \end{cases}

If a a , b b , and c c are real numbers in an arithmetic progression, then the one value of a a that can never make the above system of equations consistent is p q \dfrac{p}{q} , where p p and q q are both positive integers.

Find p + q p + q .

Inspiration


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

K T
Jun 13, 2019

A nice and original problem!

From the arithmetic progression it follows that a + c 2 b = 0 a+c-2b=0 , so that x + y + x 3 + y 3 2 x 2 2 y 2 = 0 x+y+ x^3+y^3 - 2x^2-2y^2=0 .

Using y = a x y=a-x gives a quadratic polynomial in x ( 3 a 4 ) x 2 + ( 4 a 3 a 2 ) x + a + a 3 2 a 2 = 0 (3a-4)x^2+ (4a-3a^2)x + a+a^3-2a^2=0 with solution

x = 3 a 2 4 a ± ( 3 a 2 4 a ) 2 4 ( 3 a 4 ) ( a + a 3 2 a 2 ) 2 ( 3 a 4 ) x=\frac{3a^2-4a \pm \sqrt{(3a^2-4a)^2-4 (3a-4)( a+a^3-2a^2)}}{2( 3a-4)} .

We see that the denominator is 0 when a = 4 3 a=\frac{4}{3} , but this in itself just means that we do not have a quadratic polynomial. Substituting this value for a a back into the polynomial shows that also the linear term vanishes and we are left with the equation 4 3 + 64 27 32 9 = 0 \frac{4}{3}+\frac{64}{27}-\frac{32}{9}=0 , which is inconsistent indeed because 4 27 0 \frac{4}{27} \neq 0 . So a = 4 3 a=\boxed{\frac{4}{3}} indeed makes it inconsistent.

I still have a question: are x and y to be real numbers? If so, my concern is the discriminant, which has no real solutions when it is negative. It evaluates to 3 a 4 + 16 a 3 28 a 2 + 16 a -3a^4+16a^3-28a^2+16a , so that for example negative values for a a would lead to complex values for x x and y y . It may be best to always explicitly specify the domain in problems.

I edited the problem to say that a a , b b , and c c are real numbers. However, x x and y y could be complex.

David Vreken - 1 year, 12 months ago
Roni Edwin
Jun 6, 2019

Let x + y = S , x y = P x+y=S, xy =P . Then a = S , b = S 2 2 P , c = S 3 3 S P a = S, b = S^2-2P, c = S^3-3SP . If they are in an arithmetic progression then 2 b = a + c 2b=a+c , which gives S 3 3 S P + S = 2 S 2 4 P S^3-3SP+S=2S^2-4P . Solving gives us P = 2 S 2 S S 3 4 3 S P=\frac{2S^2-S-S^3}{4-3S} , so S = 3 4 S\ =\ \frac{3}{4} which gives the answer of 7.

Great solution!

David Vreken - 2 years ago

I just spent ages proving that a = 3 4 a=\frac34 can give a consistent set of equations (it can!). Your last line should be S = 4 3 S=\frac43 .

Chris Lewis - 2 years ago

Log in to reply

Yes, I agree. I missed that the first time I read the solution.

David Vreken - 2 years ago
Anand Raj
Jun 5, 2019

We can find the value of x y xy using the first and second equation. x y = a 2 b 2 xy=\frac{a^{2}-b}{2} . Also using the first and third equation we find x y xy again, x y = a 3 c 3 a = a 3 2 b + a 3 a xy=\frac{a^{3}-c}{3a}=\frac{a^{3}-2b+a}{3a} .

Equating these two values of x y xy we will get, b = a 3 2 a 3 a 4 b=\frac{a^{3}-2a}{3a-4} , but we don't want any solution of x x and y y to satisfy the given three equations, so this solution of b b should not exist, which is only possible if a = 4 3 a=\frac{4}{3} .

Great solution!

David Vreken - 2 years ago

Amazingly, the same mistake as the other posted solution - your last line should be a = 4 3 a=\frac43 .

Chris Lewis - 2 years ago

Log in to reply

Yes, I agree. I missed that the first time I read the solution.

David Vreken - 2 years ago

Ah, yeah, my bad. Sorry!

Anand Raj - 2 years ago
David Vreken
Jun 6, 2019

Since a a , b b , and c c are in an arithmetic progression, let b = a + d b = a + d and c = a + 2 d c = a + 2d . From the first two equations, it can be found that x x , y y , and z z are roots of the equation 2 u 2 2 a u + ( a 2 a d ) = 0 2u^2 - 2au + (a^2 - a - d) = 0 , which after multiplying by u u can be rearranged to u 3 = 1 2 ( 2 a u 2 ( a 2 a d ) u ) u^3 = \frac{1}{2}(2au^2 - (a^2 - a - d)u) . Therefore,

x 3 = 1 2 ( 2 a x 2 ( a 2 a d ) x ) x^3 = \frac{1}{2}(2ax^2 - (a^2 - a - d)x)

y 3 = 1 2 ( 2 a y 2 ( a 2 a d ) y ) y^3 = \frac{1}{2}(2ay^2 - (a^2 - a - d)y)

z 3 = 1 2 ( 2 a z 2 ( a 2 a d ) z ) z^3 = \frac{1}{2}(2az^2 - (a^2 - a - d)z)

which combines to

x 3 + y 3 + z 3 = 1 2 ( 2 a ( x 2 + y 2 + z 2 ) ( a 2 a d ) ( x + y + z ) ) x^3 + y^3 + z^3 = \frac{1}{2}(2a(x^2 + y^2 + z^2) - (a^2 - a - d)(x + y + z))

and after substituting the given equations gives

a + 2 d = 1 2 ( 2 a ( a + d ) ( a 2 a d ) a ) a + 2d = \frac{1}{2}(2a(a + d) - (a^2 - a - d)a)

which rearranges to

d = a ( a 1 ) ( a 2 ) 3 a 4 d = \frac{a(a - 1)(a - 2)}{3a - 4}

For d d to have a real value, a 4 3 a \neq \frac{4}{3} , and 4 + 3 = 7 4 + 3 = \boxed{7} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...